(untitled) (ARQUISUR Revista, 2012)
Local Governments of Uruguay are a recent institution-building. The country did not have a local level of government until it was approved the "Law of Decentralization and Citizen Participation", as part of a process of emergence of the territorial issue at the institutional level. This article describes the creation process, the models applied for territorial division, its current situation and state of development in terms of "Territory Project". We describe and analyze the 89 local governments (municipalities) installed in 2010 making a initial categorization, and then six case study located in five departments: Ciudad de Canelones, Las Piedras, Municipio D, Nuevo Berlin, Piriápolis and Rio Branco. We conclude that these areas provide a space to develop the territory project. From this analysis outlines the main findings and conclusions, establishing a picture of a reality so far poorly studied.